2015
DOI: 10.1186/s12906-015-0799-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity and pharmacokinetics of cisplatin in combination therapy with a traditional Chinese medicine compound of Zengmian Yiliu granules in ICR mice and SKOV-3-bearing nude mice

Abstract: BackgroundCisplatin (CDDP) is a highly effective chemotherapeutic agent used for therapy of many tumors and has been limited by its toxicity. Zengmian Yiliu granule (ZMYL), a compound preparation of traditional Chinese medicines, has been used in clinic as a complementary and alternative medicine for attenuating CDDP-induced toxicities and enhancing the tumor therapeutic effect of CDDP. The aim of the present study is to investigate hepaprotective effect of ZMYL against CDDP-induced hepatotoxicity. Further, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
2
5
0
3
Order By: Relevance
“…GSH is the most important intracellular endogenous thiol used as a free radical scavenger to clear free radicals induced by CDDP, which maintains cell integrity by avoiding oxidative damage. Elevated GSH plays an important role in protecting CDDP-induced toxicity [29]. Our results revealed reduced GSH levels in mice treated with three doses of cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…GSH is the most important intracellular endogenous thiol used as a free radical scavenger to clear free radicals induced by CDDP, which maintains cell integrity by avoiding oxidative damage. Elevated GSH plays an important role in protecting CDDP-induced toxicity [29]. Our results revealed reduced GSH levels in mice treated with three doses of cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…Cisplatin treatment is commonly associated with serious adverse effects, such as severe acute liver and kidney injury, limiting its clinical use (Gong et al, 2015). In this study, we demonstrated that AS IV protects against cisplatin-induced acute liver and kidney injury in rats through inhibiting the expression of NLRP3 and the assembly of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 66%
“…床应用受到限制主要原因之一 [91] 。临床上常采用滋补肝肾、疏肝理气、清肝利 A c c e p t e d https://engine.scichina.com/doi/10.1360/SSV-2021-0389 胆等中药联合化疗药来减轻化疗引起的肝肾毒性,取得了较满意的效果。自由基 的产生是参与顺铂毒性的关键机制之一 [92] 。谷胱甘肽(GSH)作为自由基清除 剂能清除顺铂诱导的自由基,避免细胞氧化损伤 [93] 。谷胱甘肽 S 转移酶(GST) 通过与谷胱甘肽结合,在细胞解毒中起关键作用 [94] 。升高 GSH 和 GST 在保护顺 铂引起的肝肾毒性方面发挥重要作用。研究表明,一些中药复方如琼玉膏、健脾 护肾汤、芪参益气丸、黄葵胶囊、增免抑瘤颗粒等,能有效减轻化疗引起的肝肾 毒性 [4, [95][96][97][98][99][100][101] 。琼玉膏和芪参益气丸能降低顺铂诱导的小鼠血尿素氮(BUN)和 肌酐(SCR)水平,改善肾小管病变,减少细胞凋亡,并加速肾小管细胞再生。 琼玉膏还能显著抑制顺铂介导的肾脏 TNF-α、 IL-1β mRNA 和环氧合酶-2 (COX-2) 蛋白的升高 [95,96] 。增免抑瘤颗粒、小柴胡汤、黄连解毒汤等与化疗药联用可防止…”
Section: 中药降低化疗引起的肝肾毒性 尽管顺铂等化疗药具有出色的抗癌活性, 但其严重的肾毒性和肝毒性也是临unclassified
“…和 GST 降低以及 ICR 小鼠的一些组织病理学改变 [4,97] 。 许多中药活性单体,如葛根素、姜黄素等,也被证实具有减轻化疗药诱导的 肝肾毒性作用 [102,103] 。有研究表明,顺铂在体内外均以浓度依赖性方式上调 miR-31 的水平并影响下游 Numb/Notch1 信号通路。葛根素可降低血 BUN、SCR 水平,升高血清中 GST、超氧化物歧化酶 SOD 的表达量,并通过下调 miR-31 表达抑制 Numb/Notch1 信号通路,对顺铂诱导的急性肾损伤起到保护作用 [102] 。 用姜黄素或 α-生育酚预处理可以改善铂类化疗药、 阿霉素及甲氨蝶呤诱导的肝损 伤,降低血清 ALT 和 AST 水平,恢复脂质过氧化(LPO) 、GSH、非蛋白质硫 醇(NP-SH)和蛋白羰基(PC)的水平,以及线粒体中抗氧化和呼吸链酶的活 性 [103][104][105][106][107] 。姜黄素和顺铂联合治疗还可减少顺铂诱导的肾脏细胞空泡化和坏死以 及线粒体异常 [108,109] 。这些研究为中药改善化疗药引起的肝肾毒性提供了科学依 据。 3.4 中药降低化疗引起的胃肠道反应 胃肠道副反应包括食欲不振、腹泻、恶心和呕吐,是癌症患者放化疗后最常 见的症状。中医认为,化疗药药性较烈,往往会损伤脾胃,使脾胃运化不畅,气 血生化不足,从而加剧人体正气亏虚,在脾胃上表现为脾胃气虚,气机不畅,痰 瘀互结 [110] 。临床上常以益气和胃、养益气血、燥湿化痰方法改善患者的胃肠道 A c c e p t e d https://engine.scichina.com/doi/10.1360/SSV-2021-0389 系统功能,高频使用的中药有半夏、甘草、茯苓、白术、陈皮,以性温、味甘、 归属脾胃经的药物使用最多 [111] 。半夏泻心汤对化疗药导致的腹泻、呕吐等具有 较好的疗效 [112,113] , 研究发现, 其可通过抗炎、 抗氧化 (降低组织炎症因子如 TNF-α、 IL-1β、IL-17、IL-23 等的水平,提高 SOD 活性及 Nrf2 的表达)作用改善溃疡性 结直肠炎状况 [114] 。中药活性成分木犀草素可通过激活 Nrf2 信号通路保护氧化应 激诱导的细胞损伤,进而预防化疗诱导的结直肠炎的发生 [115] 。 经典名方六君子汤在我国和日本广泛用于治疗功能性消化不良、 胃食管反流 以及癌症患者化疗引起的消化不良。研究发现,六君子汤作为一种胃饥饿素激动 剂可有效治疗顺铂等化疗药引起的消化不良和癌症厌食-恶病质综合征 [116,117] ,还 能显著改善接受近端胃切除术的胃癌患者的胃肠道不适症状和长期生活质量 [118] 。 PHY906 源自黄芩汤的配方,由四种中药组成:甘草、芍药、黄芩和大枣。一些 临床研究表明,PHY906 可提高伊立替康、5-氟尿嘧啶(5-FU)和卡培他滨等广 谱抗癌药物在结直肠癌、 肝癌和胰腺癌中的治疗指数, 增强化疗药的抗肿瘤活性, 降低胃肠道毒性如腹泻、腹部绞痛和呕吐等,但不影响化疗药的药代动力学特性 [119][120][121][122] 。 机制研究发现, PHY906 通过促进肠道祖细胞或干细胞的再生并增强 Wnt 信号通路中 Wnt3a 的活性而恢复肠道上皮成分。此外,PHY906 还可通过减少中 性粒细胞或巨噬细胞的浸润、肠道中 TNF-α 的表达以及血浆促炎因子的浓度而 发挥抗炎作用 [123,124] 。中药大多是口服用药,进入胃肠道会与微生物发生相互作 用。研究发现,中药干预可以改善大肠癌患者术后或化疗引起的肠道微生态失衡 状况,抑制有害菌、促进有益菌的生长,使肠道微生物群落的丰富程度和多样性 增加,进而对机体产生相应的影响,降低化疗引起的胃肠道毒性 [125,126]…”
Section: 血清谷丙转氨酶 (Alt) 和门冬氨酸氨基转移酶 (Ast) 水平升高, T-gsh、 R-gshunclassified